Hubungan Latihan Senam Hamil Dan Paritas Dengan Lama Waktu Persalinan Kala I Fase Aktif Pada Ibu Bersalin Di RS Karya Medika 1 Cikarang Barat Tahun 2023 - Sherly Risda Butar Butar; Herlina Simanjuntak (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
According to WHO, the incidence of prolonged labor in the world is currently estimated to occur at 17% of total births. The Indonesian Demographic and Health Survey or abbreviated (SDKI) by the National Population and Family Planning Agency reported that the majority of birth complications are long labor (30%) to facilitate the normal birth process, so pregnancy exercises are carried out to reduce the occurrence of long labor. The aim of this study was to determine the relationship between pregnancy exercise and parity with the length of labor in the first stage of labor in the active phase of women giving birth at Karya Medika 1 Hospital, West Cikarang, 2023. This type of research is quantitative analytical using a cross-sectional study design approach. Mothers giving birth at Karya Medika 1 Hospital, West Cikarang in the period January – August 2023. The population of women giving birth is 80 people. The instruments used in this research are primary data and secondary data. Data were analyzed using the chi-square test. The results show that the variables that are related to the length of labor in the first active phase of labor for women giving birth at Karya Medika 1 Hospital, West Cikarang 2023 are pregnancy exercise (p=0.002) with an OR of 10,000, and parity (p=0.039) with an OR of 0.255. The conclusion is that the variables studied (pregnancy exercise, and parity) are all related to the length of labor in the first active phase of labor in women giving birth at Karya Medika 1 Hospital, West Cikarang 2023.Researchers advise pregnant women to take care of their pregnancy and are advised to take part in a pregnancy exercise program so that the birth process runs normally. And, Karya Medika 1 Hospital Cikarang Barat is advised to continue the pregnancy exercise program in the future.